Pengaruh Pendidikan Kesehatan Berbasis Video Tentang Menopause Terhadap Pengetahuan Keluarga Ibu Premenopause - Sitanggang, Tantri Wenny; Lestari, Rini Apriyanti; Tirtawati, Gusti Ayu (POLTEKKES KEMENKES MANADO, 2023)
Background : Menopause begins with premenopause, during this time there is a decrease in the hormones estrogen and progesterone by demanding adjustments to physical and lifestyle changes that can cause health problems. Women will also experience anxiety during menopause, one of the influencing factors is family support. Research purposes :To find out whether or not video-based health education about menopause influences the knowledge of families of premenopausal mothers. Research methods : The type of research used is quantitative research designpre experiment with a planone group pre test and post test. The population in this study were family members of premenopausal women aged 40-49 years who lived in Pondok Betung Village, totaling 110 people. The sample of this research is 15 respondents, with technique quota sampling. The research instrument used a question nairepre test andpost test. Univariate and bivariate data analysis (Paired Sample T-Test). Research result :It was found that the average knowledge before being given video-based health education to family members of premenopausal mothers was 51.87 and the average after health education was 79.33. The results of data analysis obtained by 0.000 (<0.05) it can be concluded that H0 rejected or the effect of video-based health education about menopause on family knowledge of premenopausal mothers. Conclusion:There is an influence of video-based health education about menopause on the knowledge of families of premenopausal mothers in Pondok Betung Village,in 2023.